The beginning of the world in Renaissance Jewish thought : Ma'aseh bereshit in Italian Jewish philosophy and kabbalah, 1492-1535 - Ogren, Brian. (Supplements to The Journal of Jewish Thought and Philosophy, 2016)
In The Beginning of the World in Renaissance Jewish Thought , Brian Ogren offers a deep analysis of late fifteenth century Italian Jewish thought concerning the creation of the world and the beginning of time. Ogren's book is the very first to seriously juxtapose the thought of the great Jewish thinker Yohanan Alemanno, Alemanno's famed Christian interlocutor, Giovanni Pico della Mirandola, the important Iberian exegete active in Italy, Isaac Abravanel, and Abravanel's renowned philosopher son Judah, known as Leone Ebreo. By bringing these thinkers together, this book presents a new understanding of early modern uses of Jewish texts and hermeneutics. Ogren successfully demonstrates that the syntheses of philosophy and Kabbalah carried out by these four intellectuals in their quests to understand the beginning itself marked a new beginning in Western thought, characterized by simultaneous continuity and rupture.